Continuous Intravenous Ketamine for Management of Acute Pain Postoperative Laparotomy with Septic Shock: A Case Report - Sri Ayu Nugrainy; Charles Wijaya Tan (HM Publisher, 2023)
Introduction: Ketamine used for patients in the intensive care unit provides a combination of sedation and analgesia as well as a beneficial effect on hemodynamics. This study aims to describe the use of continuous intravenous ketamine as postoperative laparotomy pain management in septic shock. Case presentation: A man, 55 years old, came to the emergency room with complaints of abdominal pain accompanied by bloating, nausea, and vomiting. From the anamnesis and physical examination and support, a diagnosis of peritonitis generalisata et causa hernia suspect incarceration was found. In postoperative observation, vital sign examination showed blood pressure 80/50, pulse 128x/minute, respiratory rate 24x/minute, temperature 37.7ºC, and numeric rating scale 5/10. The treatment the patient got was simple oxygen mask 6-7 L/ minutes, IVFD ringer lactate 3000 cc/24 hours, intravenous ceftriaxone 1gr/12 hours, intravenous metronidazole 500 mg/8 hours, norepinephrine 0.15-0.2 mcg/kg/minute titration, dobutamine 7.5 mcg/kg/minute titration, fentanyl 0.5 mcg/kg/hour titration, ketamine 0.08-0.1 mg/kg/hour and intravenous paracetamol drips 1gr/ 6 hours. The patient experienced improvement and decreased the need for postoperative fentanyl analgesia from 0.5 mcg to 0.3 mcg/kg/hour. Conclusion: The addition of continuous ketamine for acute pain management has been shown to reduce opioid requirements in critically ill patients. The combination of low doses of ketamine together with continuous opioids resulted in a lower pain scale and decreased cumulative use of opioids.